2016
DOI: 10.1080/01443615.2016.1174821
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance of IL-6 and IL-8 in tubal ectopic pregnancy

Abstract: As there are no specific non-invasive markers for the diagnosis of tubal ectopic pregnancy, our objective in the present study was to explore the role of inflammatory cytokines IL-6 and IL-8 in the diagnosis of ruptured tubal ectopic pregnancy. Twenty-eight women with tubal ectopic pregnancy, 31 patients with intrauterine abortion and 29 gestational age matched women having normal intrauterine pregnancy were included in the study. Five millilitre of blood was collected at the time of admission, serum was separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…We found that serum TNF-α and IL-6 were expressed significantly higher in patients with salpingitis and tubal pregnancy, which supported previous studies [25, 26]. They were expressed more in women with ectopic pregnancy than normal pregnancy or miscarriage.…”
Section: Discussionsupporting
confidence: 91%
“…We found that serum TNF-α and IL-6 were expressed significantly higher in patients with salpingitis and tubal pregnancy, which supported previous studies [25, 26]. They were expressed more in women with ectopic pregnancy than normal pregnancy or miscarriage.…”
Section: Discussionsupporting
confidence: 91%
“…[53]. Another study found potential utility of serum IL-6 and IL-8 in diagnosing ectopic pregnancy, as compared to normal intrauterine pregnancy and miscarriage [54]. However, this study only found IL-6 to yield remarkable sensitivity and specificity for ectopic pregnancy diagnosis at a cutoff of 26.48 pg/mL and did not find IL-8 to be significantly predictive of the condition at any cutoff.…”
Section: Role Of Cytokines and Their Clinical Cutoffs In Obstetricmentioning
confidence: 73%
“…(Dominguez et al, 2005). Another study found the potential utility of IL-8 in diagnosing an ectopic pregnancy, as compared to normal intrauterine pregnancy and miscarriage (Rajendiran et al 2016). In contrast to, Rausch et al (2012).…”
Section: Interleukinmentioning
confidence: 97%